2010
DOI: 10.1177/1934578x1000501031
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS Analysis and Antimicrobial Activity of the Essential Oil of Fresh Leaves of Eucalytus Globulus, and Leaves and Stems of Smyrnium Olusatrum from Constantine (Algeria)

Abstract: The essential oils of fresh leaves of Eucalyptus globulus L. (Myrtaceae), and leaves and stems of Smyrnium olusatrum L. (Apiaceae), obtained by hydrodistillation in a Clevenger-type apparatus, were analyzed by GC/MS. Twenty compounds were characterized, representing 98.3% of the essential oil of E. globulus, with 1,8-cineole (48.6%), globulol (10.9%), trans-pinocarveol (10.7%), and α-terpineol (6.6%) as main components, while thirty-three compounds were characterized, representing 94.3% of the essential oil of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…time of the GC run). In contrast, the essential oil from fresh leaves and stems of S. olusatrum growing in Algeria was found to contain sabinene (27.1%) and methyl‐1‐benzyl‐2‐oxocyclooctane (12.3%), which were not detected in Italian populations. In addition Portuguese populations showed a different composition, with β‐phellandrene (42.7–63.3%) as the major volatile component of flowers and ripe fruits, and 1β‐acetoxyfuranoeudesm‐4(15)‐ene was not detected at all in fruits .…”
Section: Resultssupporting
confidence: 58%
“…time of the GC run). In contrast, the essential oil from fresh leaves and stems of S. olusatrum growing in Algeria was found to contain sabinene (27.1%) and methyl‐1‐benzyl‐2‐oxocyclooctane (12.3%), which were not detected in Italian populations. In addition Portuguese populations showed a different composition, with β‐phellandrene (42.7–63.3%) as the major volatile component of flowers and ripe fruits, and 1β‐acetoxyfuranoeudesm‐4(15)‐ene was not detected at all in fruits .…”
Section: Resultssupporting
confidence: 58%
“…On the other hand, GCbased literature data, concerning the amount of isofuranodiene in S. olusatrum essential oils, showed variability ranging from its absence in populations from Algeria (Daroui-Mokaddem et al, 2010), Portugal and Italy (Marongiu et al, 2011) to $20% in populations from England (Mölleken et al, 1998a), Italy (Bertoli et al, 2004) and Corsica (Baldovini et al, 2001). Our results showed that liquid chromatography is more reliable for quantitative determination of heat-sensitive compounds in essential oils than is traditional gas chromatographic analysis.…”
Section: Hplc Analysismentioning
confidence: 45%
“…It is interesting to note that some of the previous papers (Daroui-Mokaddem et al, 2010;Marongiu et al, 2011) reported only curzerene as the major volatile in the essential oils of Fig. 3.…”
Section: Gc Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…AEO and isofuranodiene were also able to induce apoptosis in HCT116 colon cancer cells evidenced by DNA fragmentation, phosphatildyserine externalization and elevated caspase‐3 activation . AEO has also been evaluated in terms of antimicrobial activity, however, the results of different studies are controversial showing very different effects even when tested on the same species . Recently, isofuranodiene was shown to possess neuritogenic activity in vitro and hepatoprotective effects in vivo .…”
Section: Introductionmentioning
confidence: 99%